MUTATION OF CODON 306 embB GENE CLINICAL ISOLATES R9 AND L25 MULTIDRUG RESISTANT Mycobacterium tuberculosis - Nugraha Mazaafrianto, Donny
Tuberculosis (TB) is an infectious and contagious disease caused by a bacterial pathogen Mycobacterium tuberculosis (M. tuberculosis). The bacteria are spread through the air when patients cough, sneeze, talk or spit droplets contaminated with M. tuberculosis. A person can be exposed simply by inhaling small amounts of bacteria. According to WHO, a third of the world population is infected with TB and Indonesia ranks at the thirds in the world's TB cases. The emergence of multidrug- resistant strains of M. tuberculosis (MDR-M. tuberculosis) due to irregular and exhaustive in treatment, adding difficulties to overcome this disease. TB bacteria are classified as MDR-M. tuberculosis strains that were resistant to at least two drugs, rifampicin and isoniazid. Strains of MDR-M. tuberculosis can also resistant to other drugs, such as pyrazinamide, ethambutol, and streptomycin. Based on literature study and the results of previous researchers, the nature of ethambutol resitance allegedly incurred due to a gene mutation encoding a arabinosil transferase. This enzyme plays a role in the formation of cell walls of M. tuberculosis. Biochemistry Laboratory at ITB had a collection of 42 clinical isolates of MDR-M. tuberculosis that are resistant to the nature of phenotypes showed first-line TB drugs by genotype but not yet fully characterized, especially in isolates that are resistant to ethambutol. The purpose of this study to obtain information on the cause of ethambutol resistance in isolates R9 and L25, MDR-M. tuberculosis from our collection.